High-performance graphene fiber heat-conducting gasket and preparation method thereof
Through the continuous centrifugal casting film process, the polymer matrix fully penetrates into the grooves on the surface of the graphene fiber, and the graphene fiber is oriented and densified by shear force, which solves the bottleneck of the interface of the carbon fiber-based thermal conductivity gasket. Problem, the preparation of high-performance graphene fiber thermal gaskets is realized.
Patent Information
- Application Number
- CN202411406483.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing carbon fiber-based thermal conductivity gaskets have holes in the material interface, resulting in a significant increase in the interface thermal resistance. There is a bottleneck in the thermal conductivity of the carbon fiber itself, making it difficult to effectively improve the overall thermal conductivity of the material.
The continuous centrifugal casting film process is adopted to allow the polymer matrix to fully penetrate into the grooves on the surface of graphene fibers under the action of centrifugal force, reduce the interface thermal resistance, and oriented and densified graphene fibers through shear force to improve thermal conductivity.
It significantly reduces the interface thermal resistance between the thermally conductive reinforced phase and the polymer matrix, improves the bulk thermal conductivity of the material (1200~1400 W m-1 K-1), and improves the flexibility and compression modulus of the material.
Smart Images

Figure CN119463816A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal management materials, and in particular relates to a high-performance graphene fiber thermally conductive pad and a preparation method thereof. Background Art
[0002] Thermal Interface Materials (TIMs) are thermal management materials used to fill the tiny gaps between heat sources and heat sinks to promote heat transfer at the interface. They are widely used in electronic devices to prevent performance degradation or damage caused by overheating of components. Common TIMs include but are not limited to thermal paste, thermal adhesive, thermal pads, metal-based composite materials, etc. The main function of TIMs is to provide a continuous thermal conduction path so that heat can be effectively transferred from the heat source (such as a processor chip) to the heat sink or other cooling device. An ideal TIM should have high thermal conductivity, low interface thermal resistance, and good mechanical stability.
[0003] Carbon fiber has shown great application potential in the field of thermal interface materials due to its excellent axial thermal conductivity and corrosion resistance. When carbon fiber is compounded with a polymer matrix, the overall thermal conductivity of the material can be significantly improved. In addition, since carbon fiber also has the characteristics of light weight and high strength, TIMs made of them are light in weight and have good physical and mechanical properties, making them suitable for portable electronic devices.
[0004] In order to obtain carbon fiber thermal conductive gaskets with high out-of-plane thermal conductivity, external electric or magnetic fields are usually used to align carbon fibers in a specific direction, and then the composite polymer matrix is cured to form a high-performance thermal conductive gasket. These methods can effectively regulate the orientation of carbon fibers and thus improve the thermal conductivity of the material in a specific direction, but there are still some key issues that need to be addressed: (1) The interaction between carbon fibers and polymer matrix is weak, and holes are generated at the material interface during the curing process, resulting in a significant increase in the interface thermal resistance; (2) The bulk thermal conductivity of commonly used carbon fibers is generally lower than 600 W m -1 K -1 , imported high-performance products are less than 900 W m -1 K -1 , there is an upper limit to performance improvement. Summary of the invention
[0005] In view of the fact that existing carbon fiber-based thermal conductive gaskets cannot solve the problem of interface defects between carbon fiber and matrix materials, and the problem that the thermal conductivity of carbon fiber itself has a bottleneck, the present invention provides a method for preparing a high-performance graphene fiber thermal conductive gasket. The method uses a continuous centrifugal film casting process and uses the centrifugal force generated during the centrifugation process to allow the matrix material (silicone) to fully penetrate the surface grooves of the graphene fiber, thereby reducing the interfacial thermal resistance between it and the thermally conductive enhanced phase. According to tests, the polymer matrix and the graphene fiber are tightly combined, and the area of the interface gap in the entire material cross section accounts for less than 0.01%. At the same time, the shear force generated during the centrifugation process allows the graphene fiber to be further stretched and densified during the orientation process, breaking through the upper limit of thermal conductivity (1000~1400 W m -1 K -1 ). The graphene fiber / silicone composite sheet material obtained by centrifugal casting is sliced to obtain a graphene fiber thermal conductive gasket, which has the advantages of high thermal conductivity, good flexibility, and low compression modulus. Its bulk thermal conductivity ranges from 66.3 to 193.5 W m -1 K -1 When the applied pressure is 50 psi, the equivalent thermal conductivity ranges from 37.1 to 86.8 W m -1 K -1 , tensile strength greater than 1 MPa, Shore hardness range 20~60 HA.
[0006] The aforementioned preparation method specifically comprises the following steps: (1) Graphene staple fibers with a length of 200 μm to 2 mm, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst and an inhibitor are uniformly mixed to form a precursor material; the mass ratio of the vinyl silicone oil, hydrogen-containing silicone oil, the catalyst and the inhibitor is (1-260):1:(0.02-0.12):(0.01-0.1); the mass fraction of the graphene staple fibers in the precursor material is 5-60%; the density of the graphene fibers is 1.3-1.5 g cm -3 , thermal conductivity range is 900~1200 W m -1 K -1 .
[0007] (2) A PET film is attached to the inner wall of a horizontally placed centrifugal drum as a substrate, and the above-mentioned precursor material is sprayed on the inner wall of the rotating drum to form a film. During the film formation, the graphene short fibers are induced to be oriented on the surface of the substrate by the centrifugal shear force and are stretched in the orientation direction and gradually densified. At the same time, the silica precursor fully penetrates into the surface grooves of the graphene fibers under the action of centrifugal force and is initially solidified. After a certain period of time, a highly oriented graphene fiber / silicone composite sheet of the desired thickness is obtained.
[0008] (3) The sheets obtained in step 2 are stacked layer by layer and hot pressed to allow the semi-cured silicone to bond with each other and be shaped, thereby obtaining a highly oriented graphene fiber / silicone composite block.
[0009] (4) Cutting the graphene fiber / silicone composite block in a direction perpendicular to the graphene fiber orientation direction, at a cutting rate of 0.1 to 5 mm / min and a cutting interval of 200 μm to 5 mm, to obtain a high-performance graphene fiber thermal conductive pad with a thickness of 200 μm to 5 mm. The vertical cutting direction in the present invention refers to a cutting direction that is 80 to 90 degrees to the axial direction of the graphene fiber. o horn.
[0010] The thickness of a single sheet is controlled by the spraying rate and spraying time, and the orientation and densification of graphene fibers are controlled by the drum speed. In general, the spraying rate is 1~50 mL min -1 The time is 1-120 min, the roller speed range is 2000-5000 rpm; the single sheet range is 5 μm~ 3 cm; the hot pressing (the pressure is 10-100 psi, the temperature is 60-100 o C, hot pressing time 30-240 min) and the overall density was 1.62-1.92 g cm -3 .
[0011] The present invention also provides a high-performance graphene fiber thermally conductive gasket, which consists of a thermally conductive enhanced phase and a polymer matrix phase, wherein the thermally conductive enhanced phase is oriented graphene fibers, and the polymer matrix phase is silica gel.
[0012] Furthermore, the relative cross-sectional profile of the oriented graphene fiber is between 0.4 and 0.6, and the thermal conductivity is not less than 1200 W m -1 K -1 The angle between the direction of the graphene fiber and the thickness direction of the thermal pad is 80~90 o .
[0013] Furthermore, the density of the oriented graphene fiber is 1.4-1.8 g cm -3 , the oxygen content is less than 1%, the crystal size range is 50~200 nm, and the diameter is 5~20 μm.
[0014] Furthermore, the interface voids between the thermal conductivity enhancing phase and the polymer matrix phase account for less than 0.01% of the area of the entire material cross section.
[0015] Furthermore, the silica gel is formed by in-situ polymerization of vinyl silicone oil and hydrogen-containing silicone oil, and has a Shore hardness of 10-50 HA.
[0016] Furthermore, the density of the thermal pad is 1.62~1.92 g cm -3 , the mass fraction of oriented graphene fibers is 5~60%.
[0017] Furthermore, the thermal conductivity of the thermal pad ranges from 66.3 to 193.5 W m -1 K -1 When the applied pressure is 50 psi, the equivalent thermal conductivity ranges from 21.3 to 86.8 W m -1 K -1 , tensile strength greater than 1 MPa, Shore hardness range 20~60 HA.
[0018] The beneficial effects of the present invention are: (1) Through the continuous centrifugal casting method, the polymer matrix is fully infiltrated into the surface grooves of the graphene fiber under the action of centrifugal force. The area of the interface voids in the entire material cross-section is less than 0.01%. The surface groove area of the graphene fiber is utilized to the greatest extent to enhance the interface interaction between the thermal conductivity enhancing phase and the elastic component and reduce the thermal resistance between the two. This overcomes the high thermal resistance problem caused by the weak interface interaction between the carbon fiber and the polymer matrix in traditional processing methods.
[0019] (2) Through the continuous centrifugal casting method, the graphene fibers are oriented and stretched under the action of shear force to achieve high orientation and stacking of the graphene fibers. At the same time, the shear force generated by the centrifugal process is used to stretch the graphene fibers, causing their internal structural units to be tightly stacked, making the overall structure more compact and the cross-sectional anisotropy significantly reduced, thereby improving their bulk thermal conductivity (1200~1400 W m -1 K -1 ), further breaking through the upper limit of thermal conductivity of traditional asphalt-based carbon fibers and original graphene fibers, achieving a performance breakthrough in ultra-high thermal conductivity graphene fiber-based thermal interface materials.
[0020] (3) The graphene fiber thermally conductive gasket prepared by the continuous centrifugal film casting method of the present invention has the advantages of higher thermal conductivity of the thermally conductive enhanced phase, lower interface thermal resistance, higher orientation degree, and wider adjustable array density range. On the one hand, while maintaining the same thermal conductivity as traditional carbon fiber-based thermal interface materials, the carbon fiber filling amount can be greatly reduced, thereby reducing material costs and optimizing electrical performance; on the other hand, by preparing a thermally conductive enhanced phase with the same or higher carbon fiber array density, the preparation of ultra-high directional thermal conductive carbon fiber-based thermal interface materials can be achieved, meeting the heat dissipation requirements in high-end application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope photo of the microscopic morphology of the graphene fiber thermal conductive pad of Example 1; Figure 2This is a scanning electron microscope photo of the microscopic morphology of the graphene fiber thermal conductive pad of Example 2; Figure 3 This is a scanning electron microscope photo of the microscopic morphology of the graphene fiber thermal conductive pad of Example 3; Figure 4 This is a scanning electron microscope photograph of the microscopic morphology of the graphene fiber thermal conductive gasket of Example 4. DETAILED DESCRIPTION
[0022] The present invention provides a method for preparing a high-performance graphene fiber thermally conductive pad, which uses a continuous centrifugal film casting process. During the continuous centrifugal film casting process, the polymer matrix is prompted to fully penetrate into the grooves on the surface of the graphene fiber, the groove area on the surface of the graphene fiber is effectively utilized, and the interface thermal resistance between the thermally conductive enhanced phase and the second elastic component is reduced. The graphene fiber produces a drafting densification effect under the action of shear force, which not only reduces the relative cross-sectional profile, improves the orientation of the fiber, but also significantly improves the thermal conductivity of the material. After the centrifugal drafting process, the polymer matrix and the graphene fiber are more closely bonded, and the area ratio of the interface void on the entire material cross section is reduced to less than 0.01%. Since the graphene fiber surface has a rich wrinkle microstructure, it is easy to have a problem of poor interface fusion when compounded with a polymer material, resulting in a high ratio of interface voids on the material cross section. However, through the centrifugal drafting process, the polymer can more effectively penetrate into the grooves on the surface of the graphene fiber, significantly reducing the number of interface voids, achieving effective bonding between materials, thereby greatly reducing the internal thermal resistance and effectively improving the overall thermal conductivity of the material.
[0023] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0025] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. The terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0027] In the description of the present invention, “plurality” means two or more than two, unless clearly defined otherwise.
[0028] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0029] In addition, the technical terms involved in the present invention are explained as follows: As is common knowledge in the art, the relative cross-sectional profile is determined by referring to the standard FZ / T 50002-1991. The relative cross-sectional profile is calculated by measuring the radius of the inscribed circle (r) of the magnified cross-sectional profile of the shaped fiber and the radius of the circumscribed circle (R) on the corresponding cross-sectional profile concentric with r. 2 -r 2 ) / R 2 *100%. The crystal size of graphene fiber was tested by X-ray diffraction method. The grain size was calculated by Scherrer equation according to the shape and position of the diffraction peak. The area ratio of interface voids in the entire material cross section was obtained by Image-J statistics. Shore hardness was tested according to GB / T 531.1-2008.
[0030] The bulk thermal conductivity is tested by laser flash method, refer to GB / T 22588-2008. Thermal impedance is the sum of the thermal resistance of the material itself and the thermal resistance between the contact surface, and is tested by ASTM D 5470 method, and the equipment is LW-9389MD interface material thermal resistance and thermal conductivity meter.
[0031] Embodiment 1: (1) Use a tube cutter to cut the graphene fiber filament into short fibers with a length of 1 mm, add vinyl silicone oil, hydrogenated silicone oil, platinum-vinyl siloxane complex and ethynyl cyclohexanol in a ratio of 3:1:0.02:0.01, and control the mass fraction of graphene fiber to be 20%. Place the material in a homogenizer for homogenization for 30 min and degas for 5 min. The density of the graphene fiber is 1.5 g cm -3 , thermal conductivity is 1203 W m -1 K -1 .
[0032] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 20 mL min -1 , the roller speed was 5000 rpm, and after spraying for 25 min, an oriented graphene fiber / silicone composite sheet with a thickness of 2.4 mm was obtained.
[0033] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is subjected to specific pressure and temperature to make the semi-cured silicone adhere to each other and then completely set to obtain a highly oriented graphene fiber / silicone composite block. The applied pressure is 50 psi and the heating temperature is 80 o C, hot pressing time is 120 min.
[0034] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 0.2 mm / min, and the cutting spacing is 1 mm.
[0035] The obtained graphene fiber thermal conductive pad has a thickness of 1 mm and a density of 1.77 g cm -3 The tensile strength is 5.8 MPa, the Shore hardness is 31.5 HA, and the thermal conductivity of a single graphene fiber after centrifugal drawing is measured by the T-type method after removing the silica gel matrix using a silica gel solvent. The result is 1401.3 W m -1 K -1 , oxygen content is 0.8%, crystal size range is 50nm, diameter is 8 μm, density is 1.8 g cm -3 The relative cross-sectional profile is 0.4. The microstructure of the thermal conductive pad is as follows: Figure 1 As shown in the figure, it can be found that the graphene fibers are highly oriented along the thickness direction, and the angle between the direction of the graphene fibers and the thickness direction of the thermal pad is between 80 and 90 degrees. oThe interfacial voids are evenly distributed in the silicone matrix and fit closely to the silicone matrix. The area of the interfacial voids in the entire material cross section accounts for less than 0.01%. The thermal conductivity of the thermal pad out of the surface is measured by transient laser flash method to be 143.5 Wm -1 K -1 The steady-state method measured the compressibility at 50 psi to be 51%, and the equivalent thermal conductivity to be 83.1 W m -1 K -1 , thermal impedance is 0.059K cm 2 W -1 .
[0036] Embodiment 2: (1) The graphene fiber filaments were cut into short fibers with a length of 200 μm using a tube cutter, and vinyl silicone oil, hydrogenated silicone oil, platinum-divinyltetramethyldisiloxane complex and 3-ethynylcyclohexanol were added in a ratio of 1:1:0.02:0.01, and the mass fraction of the graphene fiber was controlled to be 5%. The material was placed in a homogenizer for homogenization for 60 min and degassed for 10 min. The density of the graphene fiber was 1.3 g cm -3 , thermal conductivity is 900 W m -1 K -1 .
[0037] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 1 mL min -1 , the roller speed was 2000 rpm, and after spraying for 120 min, an oriented graphene fiber / silicone composite sheet with a thickness of 0.58 mm was obtained.
[0038] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is subjected to specific pressure and temperature to make the semi-cured silicone adhere to each other and then completely set to obtain a highly oriented graphene fiber / silicone composite block. The applied pressure is 10 psi and the heating temperature is 60 o C, hot pressing time is 30 min.
[0039] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 0.1 mm / min, and the cutting spacing is 1 mm.
[0040] The obtained graphene fiber thermal conductive pad has a thickness of 1 mm and a density of 1.69 g cm-3 The tensile strength is 3.9 MPa, the Shore hardness is 20.0 HA, and the thermal conductivity of a single graphene fiber after centrifugal drawing is measured by the T-type method after removing the silica gel matrix using a silica gel solvent. The result is 1200.6 W m -1 K -1 , oxygen content is 0.74%, crystal size range is 100 nm, diameter is 5 μm, density is 1.4 g cm -3 The relative cross-sectional profile is 0.6. The thermal conductivity of the thermal pad out of the plane is 66.3 W m-2 measured by transient laser flash method. -1 K -1 The steady-state method measured the compressibility at 50 psi to be 62%, and the equivalent thermal conductivity to be 21.3 W m -1 K -1 , thermal impedance is 0.178 K cm 2 W -1 .
[0041] Embodiment 3: (1) The graphene fiber filaments were cut into short fibers with a length of 1 mm using a tube cutter, and vinyl silicone oil, hydrogenated silicone oil, platinum-vinylsiloxane complex and 3,5-dimethyl-1-ethynylcyclohexanol were added in a ratio of 120:1:0.08:0.05, and the mass fraction of the graphene fiber was controlled to be 60%. The material was placed in a homogenizer for homogenization for 30 min and degassed for 5 min. The density of the graphene fiber was 1.48 g cm -3 , thermal conductivity range is 1248 W m -1 K -1 .
[0042] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 50 mL min -1 , the roller speed was 5000 rpm, and after spraying for 1 min, an oriented graphene fiber / silicone composite sheet with a thickness of 0.25 mm was obtained.
[0043] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is completely shaped by applying a specific pressure and temperature to make the semi-cured silicone bond to each other, thereby obtaining a highly oriented graphene fiber / silicone composite block. The applied pressure is 50 psi and the heating temperature is 100 o C, hot pressing time is 240 min.
[0044] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 0.5 mm / min, and the cutting spacing is 0.2 mm.
[0045] The obtained graphene fiber thermal conductive pad has a thickness of 0.2 mm and a density of 1.65 g cm -3 The tensile strength is 3.3 MPa, the Shore hardness is 46.0 HA, and the thermal conductivity of a single graphene fiber after centrifugal drawing is measured by the T-type method after removing the silica gel matrix using a silica gel solvent. The result is 1491.1 W m -1 K -1 , with a density of 1.75 g cm -3 , oxygen content 0.45%, crystal size 200 nm, diameter 7.5 μm, relative cross-sectional profile 0.43. The microstructure of the thermal conductive pad is shown in Figure 2 As shown in the figure, it can be found that the graphene fibers are highly oriented along the thickness direction, evenly and densely distributed in the silicone matrix, and closely fit with the silicone matrix, with no obvious stratification at the interface. The out-of-plane thermal conductivity of the thermal conductive pad measured by the transient laser flash method is 193.5 Wm -1 K -1 The steady-state method measured the compressibility at 50 psi to be 31%, and the equivalent thermal conductivity to be 49.7 W m -1 K -1 , thermal impedance is 0.028K cm 2 W -1 .
[0046] Embodiment 4: (1) The graphene fiber filaments were cut into short fibers with a length of 1 mm using a tube cutter, and vinyl silicone oil, hydrogenated silicone oil, platinum-cyclohexyldimethylsiloxane complex and 3-ethynylcyclohexanol were added in a ratio of 260:1:0.12:0.1, and the mass fraction of the graphene fiber was controlled to be 40%. The material was placed in a homogenizer for homogenization for 30 min and degassed for 5 min. The density of the graphene fiber was 1.5 g cm -3 , thermal conductivity range is 1203 W m -1 K -1 .
[0047] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 1 mL min -1, the roller speed was 4000 rpm, and after spraying for 1 min, an oriented graphene fiber / silica gel composite sheet with a thickness of 20 μm was obtained.
[0048] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is subjected to specific pressure and temperature to make the semi-cured silicone adhere to each other and then completely set to obtain a highly oriented graphene fiber / silicone composite block. The applied pressure is 100 psi and the heating temperature is 90 o C, hot pressing time is 120 min.
[0049] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 5 mm / min and the cutting spacing is 5 mm.
[0050] The obtained graphene fiber thermal conductive pad has a thickness of 5 mm and a density of 1.65 g cm -3 The tensile strength is 7.5 MPa, the Shore hardness is 41.2 HA, and the thermal conductivity of a single graphene fiber after centrifugal drawing is measured by the T-type method after removing the silica gel matrix using a silica gel solvent. The result is 1499.8 W m -1 K -1 , with a density of 1.83 g cm -3 , oxygen content of 0.86%, crystal size range of 70 nm, diameter of 20 μm, relative cross-sectional profile of 0.48. The graphene fibers are highly oriented along the thickness direction, evenly and densely distributed in the silicone matrix, and closely fit with the silicone matrix, with no obvious stratification at the interface. The out-of-plane thermal conductivity of the thermal conductive pad was measured by transient laser flash method to be 166.1 W m -1 K -1 The steady-state method measured the compression rate at 50 psi to be 45%, and the equivalent thermal conductivity to be 86.8 W m -1 K -1 , thermal impedance is 0.32 K cm 2 W -1 .
[0051] Comparative Example 1: (1) The graphene fiber filaments were cut into short fibers with a length of 200 μm using a tube cutter, and vinyl silicone oil, hydrogenated silicone oil, platinum-divinyltetramethyldisiloxane complex and 3-ethynylcyclohexanol were added in a ratio of 1:1:0.02:0.01, and the mass fraction of the graphene fiber was controlled to be 5%. The material was placed in a homogenizer for homogenization for 60 min and degassed for 10 min. The density of the graphene fiber was 1.3 g cm -3 , thermal conductivity is 900 W m-1 K -1 .
[0052] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 1 mL min -1 , the roller speed was 500 rpm, and after spraying for 120 min, an oriented graphene fiber / silicone composite sheet with a thickness of 0.7 mm was obtained.
[0053] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is subjected to specific pressure and temperature to make the semi-cured silicone adhere to each other and then completely set to obtain a highly oriented graphene fiber / silicone composite block. The applied pressure is 10 psi and the heating temperature is 60 o C, hot pressing time is 30 min.
[0054] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 0.1 mm / min, and the cutting spacing is 1 mm.
[0055] The obtained graphene fiber thermal conductive pad has a thickness of 1 mm and a density of 1.67 g cm -3 The tensile strength is 3.2 MPa, the Shore hardness is 16.5 HA, and the thermal conductivity of a single graphene fiber after centrifugal drawing is measured by the T-type method after removing the silica gel matrix using a silica gel solvent. The result is 923.6 W m -1 K -1 , with a density of 1.33 g cm -3 The crystal size range is 30 nm, the diameter is 11 μm, and the relative cross-sectional profile is 0.63. It can be found that compared with Example 2, the lower centrifugal speed only increases the carbon fiber density by 0.03 g cm -3 In addition, the higher fiber profile means that the densification effect of carbon fiber is relatively poor.
[0056] The microstructure of the thermal conductive pad is as follows: Figure 3 As shown in the figure, it can be found that when the roller speed is low during the centrifugal casting process, the graphene fiber orientation is poor, the array density is low, and there is an obvious interface layer between the graphene fiber and the silica gel substrate. The out-of-plane thermal conductivity measured by the transient laser flash method is 41.3 W m -1 K -1The compressibility was 64% at 50 psi using the steady-state method, and the equivalent thermal conductivity was 11.3 W m -1 K -1 , thermal impedance is 0.318 K cm 2 W -1 .
[0057] Comparative Example 2: (1) The graphene fiber filaments were cut into short fibers with a length of 1 mm using a tube cutter, and vinyl silicone oil, hydrogenated silicone oil, platinum-divinyltetramethyldisiloxane complex and 3-ethynylcyclohexanol were added in a ratio of 260:1:0.12:0.1, and the mass fraction of the graphene fiber was controlled to be 30%. The material was placed in a homogenizer for homogenization for 30 min and degassed for 5 min. The density of the graphene fiber was 1.5 g cm -3 , thermal conductivity is 1200 W m -1 K -1 .
[0058] (2) Using a continuous centrifugal coating device, a PET film was attached to the inner wall of a horizontally placed drum as a substrate. The drum used had a circumference of 2 m and a width of 0.1 m. The mixed graphene fiber / silicone precursor material was transported by a delivery pump and sprayed on the inner wall of the rapidly rotating drum through a nozzle at a spray rate of 50 mL min -1 , the roller speed was 3000 rpm, and after spraying for 140 min, an oriented graphene fiber / silicone composite sheet with a thickness of 45 mm was obtained.
[0059] (3) The highly oriented graphene fiber / silicone composite sheet obtained in the layer-by-layer stacking step (2) is subjected to specific pressure and temperature to make the semi-cured silicone adhere to each other and then completely set to obtain a highly oriented graphene fiber / silicone composite block. The applied pressure is 10 psi and the heating temperature is 80 o C, hot pressing time is 120 min.
[0060] (4) Cutting the graphene fiber / silica gel composite block obtained in step (3) in a direction that is 90 degrees to the orientation direction of the graphene fiber. o , the cutting rate is 0.2 mm / min, and the cutting spacing is 1 mm.
[0061] The obtained graphene fiber thermal conductive pad has a thickness of 1 mm and a density of 1.62 g cm -3, tensile strength is 2.9 MPa, Shore hardness is 37 HA, and after using silica gel solvent to remove the silica gel matrix, it is found that the diameter of graphene fibers is highly inconsistent, ranging from 5 to 10 μm, and the relative cross-sectional profile of the fibers is generally higher than 0.65. The microscopic morphology of the obtained thermal conductive pad is shown in Figure 4 As shown in the figure, the graphene fibers are generally oriented in the thickness direction, and there is a certain degree of stratification between them and the silica gel matrix. The regularity of the fiber cross section is poor. This is because the spraying time is too long and the spraying amount is too large, resulting in a large deviation in the centrifugal force received by the graphene fibers in the thickness direction. The centrifugal force received by the graphene fibers near the center of the drum is small, and densification cannot be effectively achieved. The out-of-plane thermal conductivity of the thermal conductive pad measured by the transient laser flash method is 58.7 W m -1 K -1 The compressibility at 50 psi was 43.7% using the steady-state method, and the equivalent thermal conductivity was 14.4 W m -1 K -1 , thermal impedance is 0.39 K cm 2 W -1 .
[0062] Although the embodiments of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments.
Claims
1. A method for preparing a high-performance graphene fiber thermally conductive pad, characterized in that: The following steps are involved: (1) Graphene short fibers with a length of 200 μm to 2 mm, vinyl silicone oil, hydrogen-containing silicone oil, a catalyst and an inhibitor are uniformly mixed to form a precursor material; the mass ratio of the vinyl silicone oil, hydrogen-containing silicone oil, the catalyst and the inhibitor is (1-260):1:(0.02-0.12):(0.01-0.1); the mass fraction of the graphene short fibers in the precursor material is 5-60%; (2) A PET film is attached to the inner wall of a horizontally placed drum as a substrate, and a precursor material is sprayed on the inner wall of the rotating drum to form a film to obtain a graphene fiber / silicone sheet; (3) stacking the graphene fiber / silicone sheets layer by layer and hot pressing to obtain a graphene fiber / silicone composite block; (4) Slice the graphene fiber / silicone composite block to obtain a thermal conductive gasket with vertically oriented graphene fibers.
2. The preparation method according to claim 1, characterized in that: In step 2, the spraying rate is 1~50 mL min -1 , time is 1~120 min, and the drum speed range is 2000~5000 rpm.
3. The preparation method according to claim 1, characterized in that: In step 3, the pressure of the hot press is 10-100 psi and the temperature is 60-100 o C, hot pressing time is 30~240 min.
4. The preparation method according to claim 1, characterized in that: In step 4, the cutting rate of the slices is 0.1~5mm / min, and the cutting interval is 200 μm~5 mm.
5. The preparation method according to claim 1, characterized in that: The catalyst includes a platinum catalyst, and the inhibitor includes ethynyl cyclohexanol and its derivatives.
6. The high-performance graphene fiber thermally conductive pad prepared by the preparation method according to claim 1, characterized in that: It is composed of a thermal conductivity enhancing phase and a polymer matrix phase, wherein the thermal conductivity enhancing phase is oriented graphene fiber and the polymer matrix phase is silica gel; the interface gap between the thermal conductivity enhancing phase and the polymer matrix phase accounts for less than 0.01% of the area of the entire material cross section.
7. The thermally conductive pad according to claim 6, characterized in that: The density of the oriented graphene fiber is 1.4-1.8 g cm -3 The relative cross-sectional profile is between 0.4 and 0.6, and the angle between the direction of the graphene fiber and the thickness direction of the thermal pad is between 80 and 90 degrees. o , thermal conductivity not less than 1200 W m -1 K -1 .
8. The thermally conductive pad according to claim 6, characterized in that: The high-performance graphene fiber thermal conductive pad has a density of 1.62-1.92 g cm -3 .
9. The thermally conductive pad according to claim 6, characterized in that: The thermal conductivity of the high-performance graphene fiber thermally conductive pad ranges from 66.3 to 193.5 W m -1 K -1 , tensile strength greater than 1 MPa, Shore hardness range 20~60 HA.
Citation Information
Patent Citations
Graphene based silica gel heat-conductive gasket and preparation method thereof
CN106634863A
Graphene coating and preparation method of graphene conductive corrosion-resistant coating
CN112341848A
High-thermal-conductivity gasket and preparation method thereof
CN112409798A
Self-adhesive graphene heat-conducting gasket and preparation method thereof
CN114181639A
Preparation method of high-orientation graphene film
CN115180615A